2016
DOI: 10.1177/0022022116680481
|View full text |Cite
|
Sign up to set email alerts
|

Nature, Nurture, and Their Interplay

Abstract: Cultural neuroscience research examines how psychological processes are affected by the interplay between culture and biological factors, including genetic influences, patterns of neural activation, and physiological processes. In this review, we present foundational and current empirical research in this area, and we also discuss theories that aim to explain how various aspects of the social environment are interpreted as meaningful in different cultures and interact with a cascade of biological processes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 100 publications
(121 reference statements)
2
12
0
Order By: Relevance
“…For the sense of agency, the sharp distinction between explicit and implicit processes is incomplete: Voyer and Franks (2014) suggest that three different modalities are involved in its assessment: implicit (a “feeling” of agency), intermediate (a “perception”), and explicit (a “judgment”). The intermediate level of self- related processing is in line with recent developments in the field of cultural neuroscience (Han & Humphreys 2016; Sasaki & Kim 2017). It may involve composing complex plans and actions from less complex ones but does not, in itself, require conscious awareness of that agency (e.g., holding a cup whilst someone else is pouring a drink in it).…”
supporting
confidence: 73%
“…For the sense of agency, the sharp distinction between explicit and implicit processes is incomplete: Voyer and Franks (2014) suggest that three different modalities are involved in its assessment: implicit (a “feeling” of agency), intermediate (a “perception”), and explicit (a “judgment”). The intermediate level of self- related processing is in line with recent developments in the field of cultural neuroscience (Han & Humphreys 2016; Sasaki & Kim 2017). It may involve composing complex plans and actions from less complex ones but does not, in itself, require conscious awareness of that agency (e.g., holding a cup whilst someone else is pouring a drink in it).…”
supporting
confidence: 73%
“…For the sense of agency, the sharp distinction between explicit and implicit processes is incomplete: Voyer and Franks (2014) suggest that three different modalities are involved in its assessment: implicit (a "feeling" of agency), intermediate (a "perception"), and explicit (a "judgment"). The intermediate level of self-related processing is in line with recent developments in the field of cultural neuroscience (Han & Humphreys 2016;Sasaki & Kim 2017). It may involve composing complex plans and actions from less complex ones but does not, in itself, require conscious awareness of that agency (e.g., holding a cup whilst someone else is pouring a drink in it).…”
Section: What Does Agency Afford the Self?mentioning
confidence: 55%
“…Genetic information about the actor may, however, provide additional predictive power over and above the standard personality measures used in predicting behavior in free-response situations; research has shown that persons with certain genetic profiles seek out particular kinds of social situations and may be more responsive in these situations than others lacking these genetic profiles (see e.g., Dick et al, 2015; Salvatore and Dick, 2016). The extension of this work on genetic influence into the cross-cultural domain is in its infancy but promising in its capacity to add further predictive power to our standard measures of personality (Sasaki and Kim, 2017).…”
Section: Reclaiming the Individualmentioning
confidence: 99%
“…These genetic givens are then infused into the normative cultural realities of the specific cultural groupings encountered by the individual. Successive enculturation experiences then channel the individual’s genetic profile into a behavioral repertoire which interacts with the fortuities of life (Bandura, 1998) to further refine the individual’s motivations and beliefs about the perceived world (Sasaki and Kim, 2017). These emergent structures finally channel individual choices and skill enhancements, leading to individual personality developments compatible with the constraints and affordances of the proximal cultural systems encountered as embedded within the distal birth culture of each individual.…”
Section: Introductionmentioning
confidence: 99%